1980
DOI: 10.1080/15298668091425130
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure of laboratory mice to manganese oxide

Abstract: An acute inhalation exposure of laboratory mice to respirable Mn3O4 aerosols is described. The generation system consisted of a Wright dust generator which produced 1.40 micrometer aerosols. A non-linear loss of deposited manganese from mouse lungs over the inital 24-hour post-exposure period was observed. Systemic distribution of the manganese was observed in various tissues following exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 0 publications
1
9
0
2
Order By: Relevance
“…Following a 2-h inhalation, mean initial lung deposition was 21.7 ± 2.2 µg Mn/g lung weight, comparable to our highest level for Mn 3 O 4 of 22.8 ± 6.5 µg/g lung weight. Within 24 h, Adkins et al (1980) found that lung levels decreased to 2.98 ± 0.2 µg/g lung weight (not significantly different from control levels). Lung levels 24 h postinstillation in our study were 0.7 ± 0.5 µg/g lung weight (not significantly different from control levels).…”
Section: Manganese Pulmonary Clearance 949mentioning
confidence: 75%
See 1 more Smart Citation
“…Following a 2-h inhalation, mean initial lung deposition was 21.7 ± 2.2 µg Mn/g lung weight, comparable to our highest level for Mn 3 O 4 of 22.8 ± 6.5 µg/g lung weight. Within 24 h, Adkins et al (1980) found that lung levels decreased to 2.98 ± 0.2 µg/g lung weight (not significantly different from control levels). Lung levels 24 h postinstillation in our study were 0.7 ± 0.5 µg/g lung weight (not significantly different from control levels).…”
Section: Manganese Pulmonary Clearance 949mentioning
confidence: 75%
“…In an inhalation study of Mn 3 O 4 by Adkins et al (1980), within 24 h after a 2-h exposure to 1.8 mg/m 3 of Mn 3 O 4 in mice, approximately 14% of inhaled Mn remained in the lung. Following a 2-h inhalation, mean initial lung deposition was 21.7 ± 2.2 µg Mn/g lung weight, comparable to our highest level for Mn 3 O 4 of 22.8 ± 6.5 µg/g lung weight.…”
Section: Manganese Pulmonary Clearance 949mentioning
confidence: 99%
“…[26] Adkins et al . [27] studied an acute inhalation exposure of laboratory mice to respirable Mn3O4 aerosols and found that a systemic distribution of the manganese was observed in various tissues following exposure. Another present concern is the use of the gasoline additive methylcyclopentadienyl manganese tricarbonyl, which is documented for the generation of air manganese and can be the future problem.…”
Section: Manganese Intoxicationmentioning
confidence: 99%
“…Nach einer zweistündigen Inhalation von Mn 3 O 4 -Aerosol (1,4 Vm, 1798 mg/m 3 ) werden nach 4; 6 und 24 Stunden noch 47; 27 und 14% im Lungengewebe von weiblichen Mäusen gefunden [4]. Im Konzentrationsbereich von 0�2,9 mg Mn/m 3 besteht unter sonst identischen Versuchsbedingungen bei Mäusen, die unmittelbar nach der zweistündigen Exposition getötet wurden, eine lineare Beziehung zwischen der Mangan-Aerosolkonzentration in der Einatmungsluft und dem Mangangehalt/g getrockneter Lunge [4]. …”
unclassified
“…In einer weiteren Inhalationsstudie mit Mäusen (2 h, 1837 mg/mn/m 3 ) wurde die Gewebeverteilung 0; 24 und 48 Stunden nach der Inhalation gemessen [4]. In der Lunge finden sich zu diesen Zeitpunkten 21,7; 2,98 und 2,69 Vg Mn/g Trockengewebe.…”
unclassified